PEMBENTUKAN HARGA JAGUNG TINGKAT PRODUSEN DI PROVINSI LAMPUNG - Rati - Purwasih (Politeknik Negeri Lampung, 2020)
The study aimed to analyze factors that affect the price mechanism of corn among producers in Lampung Province. Secondary data from 2009 to 2014 used accounted 72 month of total observation. Multiple linear regression using Ordinary Least Squares was applied to answer the research question. The study found that the price mechanism of corn among producers was influenced by total production, previous period of corn price and value exchange. On the other hand, the corn price among consumers and price import of corn did not influence the corn price among producers. The corn price among producers were less responsive against the total production which was due to the existence of oligopsony power.